2015
DOI: 10.1017/pab.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

A simple way to improve multivariate analyses of paleoecological data sets

Abstract: Multivariate methods such as cluster analysis and ordination are basic to paleoecology, but the messy nature of fossil occurrence data often makes it difficult to recover clear patterns. A recently described faunal similarity index based on the Forbes coefficient improves results when its complement is employed as a distance metric. This index involves adding terms to the Forbes equation and ignoring one of the counts it employs (that of species found in neither of the samples under consideration). Analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Different analyses have shown that NMDS is as good as or better than other ordination techniques in recovering the underlying structure of the data (Minchin 1987; Bush and Brame 2010). Recently, Alroy (2015) proposed that principal coordinates analysis using a novel modification of the Forbes index was a best solution for paleoecological ordination. Using PCO and the Forbes index, or another common ordination technique such as detrended correspondence analysis, gave virtually identical results.…”
Section: Methodsmentioning
confidence: 99%
“…Different analyses have shown that NMDS is as good as or better than other ordination techniques in recovering the underlying structure of the data (Minchin 1987; Bush and Brame 2010). Recently, Alroy (2015) proposed that principal coordinates analysis using a novel modification of the Forbes index was a best solution for paleoecological ordination. Using PCO and the Forbes index, or another common ordination technique such as detrended correspondence analysis, gave virtually identical results.…”
Section: Methodsmentioning
confidence: 99%
“…The author observed few differences among results from several types of ordination and choice of coefficients, including the modified Forbes coefficient of Alroy (2015b) and Bray and Curtis dissimilarity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, to investigate the relationships between vegetation compositional change over time and to interpret the response of pollen assemblages to fire events over millennial scales, I used Kruskal's nonmetric multidimensional scaling (NMDS) to reduce the dimensionality of the dataset and map vegetation change (Alroy, 2015). This analysis was carried out using the MASS package in R and pollen data was transformed using the Bray-Curtis distance measure, a common distance metric in ecological research (Beals, 1984).…”
Section: Discussionmentioning
confidence: 99%